2014
DOI: 10.1002/2014gl059646
|View full text |Cite
|
Sign up to set email alerts
|

Compositional evidence of magmatic activity on Vesta

Abstract: Like the Earth and other terrestrial planets, the asteroid Vesta has a basaltic crust and a large iron core; its surface is dominated by impact craters of all sizes and has tectonic features. The presence of basaltic compositions, olivine, howardite-eucrite-diogenite meteorites, and models of Vesta's formation, suggests that volcanic and/or magmatic activity could have occurred on Vesta. A global search for lobate structures did not find unequivocal evidence of volcanic features. Nevertheless, several morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous works concluded that Brumalia Tholus (Numisia quadrangle) is a magmatic intrusion generated by the Rheasilvia impact (De Sanctis et al, 2014;Buczkowski et al, 2014). The Lucaria Tholus (Lucaria quadrangle) and the Aricia Tholus (Marcia quadrangle) instead have a different history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works concluded that Brumalia Tholus (Numisia quadrangle) is a magmatic intrusion generated by the Rheasilvia impact (De Sanctis et al, 2014;Buczkowski et al, 2014). The Lucaria Tholus (Lucaria quadrangle) and the Aricia Tholus (Marcia quadrangle) instead have a different history.…”
Section: Discussionmentioning
confidence: 99%
“…The Brumalia Tholus has been largely analysed by Buczkowski et al (2014) andDe Sanctis et al (2014). It consists of a magmatic intrusion, as inferred by the presence of diogenite-rich material.…”
Section: Tholimentioning
confidence: 99%
“…Outcrops of different mineralogy occur within short distances of each other (within a few kilometers), which may support the hypothesis of lateral heterogeneity of the crust. Dykes and melt plumes could explain this heterogeneity, like the case of the ejecta of Teia crater on Brumalia Tholus (De Sanctis et al, 2014;Buczkowski et al, 2014), which is interpreted as excavated material from a dike, or excavated materials from large impacts forming a patchwork, before being partially mixed and covered by smaller impacts.…”
Section: Rheasilvia and Veneneia Antipodes: No Obvious Effects In Thementioning
confidence: 99%
“…The false-colour orange and reds correspond to the ratio of 749/438 nm, and are observed to be directly related to ejecta material with a smeared and flow-like texture in the highest resolution (20 m/pixel) FC images from Dawn's Low Altitude Mapping Orbit (LAMO) (Buczkowski et al 2014). Spectral analysis by the VIR instrument has shown that while the background Vestalia Terra material is howarditic (De Sanctis et al 2012), consistent with the plateau being covered with ejecta from the large impacts surrounding it, Teia's ejecta are more diogenitic in composition (De Sanctis et al 2014). The identification of diogenite in the ejecta of Teia crater is consistent with the hill being the surface representation of a magmatic intrusion.…”
Section: The Identification Of Brumalia Tholusmentioning
confidence: 92%